The Social Construction of Fatherhood Online: A Pedagogical Analysis on Contemporary Paternal Narratives - Davide Cino (Pensa MultiMedia, 2023)
The adoption of digital media within the domestic environment has led to an increasing contribution to scholarship in the field of pedagogy, family, and media studies concerned with the use of digital technology by contemporary parents, as both a tool for self-expression and informal learning, and as a milieu where to question or reinforce narratives about what it means to be a parent. In this paper we focus on the analysis of three different Italian paternal platforms: a website from a dad and professional family mediator, a blog by a father from a heterosexual family, the social media account of two gay fathers. Building on findings from a discourse analysis, we seek to understand the pedagogical and informal learning potential of these different digital milieus and their contents, here intended as cultural objects, with respect to how and in what terms they contribute to the social and discursive construction of fatherhood.